(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract: At a time when young people make up a significant part of the world's population, it is important to recognize their influence on the changes taking place in modern countries. Young people are the biggest force, working to further improvescience, technology, and the digital world, to make innovations an integral part of people's lifestyles. States, societies, and even the world are being renewed due to their initiative and desire to innovate. It is for this reason that creating the necessaryconditions for them is being evaluated as the main goal and task by the countries of the world. Intellectual and potential youth is the biggest factor determining the status and influence of every country.